2021
DOI: 10.1002/fsn3.2319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propolis supplementation on athletic performance, body composition, inflammation, and oxidative stress following intense exercise: A triple‐blind randomized clinical trial

Abstract: Background Emerging evidence indicates that propolis as a novel potential antioxidant has unique benefits. This study aimed to evaluate the effect of propolis on oxidative stress, inflammation, body composition, and athletic performance in healthy active subjects. Methods This clinical trial was conducted on 54 male military cadets. Eligible subjects were randomly allocated to receive a single dose of 450 mg propolis twice daily for four weeks or a matching placebo containing microcrystalline cellulose. Cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Susan [ 168 ] reported the potential use of propolis as an anti-nociceptive therapy post-surgery [ 168 ]. Moreover, Soleimani [ 169 ] found that propolis supplementation reduced the pro-inflammatory cytokine IL-6 level in male military cadets subjected to Cooper 12-min run test and running-based anaerobic sprint test [ 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…Susan [ 168 ] reported the potential use of propolis as an anti-nociceptive therapy post-surgery [ 168 ]. Moreover, Soleimani [ 169 ] found that propolis supplementation reduced the pro-inflammatory cytokine IL-6 level in male military cadets subjected to Cooper 12-min run test and running-based anaerobic sprint test [ 169 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Gao et al reported that after 18 weeks of consuming Chinese propolis, a significant increase was observed in the serum GSH, flavonoids, and polyphenols of patients with type II diabetes (Gao et al, 2018). Recently Soleimani et al also observed that the administration of propolis (450 mg/kg twice daily) significantly increased the levels of GSH and TAC and decreased total oxidant status (TOS) and MDA after 4 weeks of intervention (Soleimani et al, 2021).…”
Section: Effects Of Propolis In Relation To Oxidative Stress In Ramentioning
confidence: 98%
“…We analyzed nine articles. The random sequence generation was well observed in five studies(Afsharpour et al, 2019;Darvishi et al, 2020;Gholaminejad et al, 2019;Mujica et al, 2017;Soleimani et al, 2021).…”
mentioning
confidence: 90%
“…While some studies have shown its protective effect against oxidative stress, the findings are disputed. (Afsharpour et al, 2019; Ebeid et al, 2016; Gholaminejad et al, 2019; Mujica et al, 2017; Soleimani et al, 2021), whereas significant antioxidant effects have not been observed in others (Darvishi et al, 2020; Gao et al, 2018; Zhao et al, 2016). Therefore, this systematic review and meta‐analysis were conducted to explore the effect of propolis on oxidative stress and antioxidant capacity by evaluating MDA, TAC, GSH, GPx, and SOD levels.…”
Section: Introductionmentioning
confidence: 99%